A highly efficient ZVT-ZCT PWM boost converter with direct power transfer - Sahin, Yakup; Ting, Naim Suleyman; Aksoy, Ismail (SPRINGER, 2018)
In this paper, a high-efficiency ZVT-ZCT PWM boost converter with direct power transfer is proposed. In the proposed converter, the main switch turns on with zero voltage transition and turns off with zero current transition. The main diode turns on with zero voltage switching and turns off with zero current switching. All of the other semiconductors in the converter turn on and off with soft switching. There is no extra current or voltage stress on the main semiconductors. The most important feature of the proposed converter is that it has direct power transfer. So, the efficiency of converter can be increased. Also, it has features as low cost, simple structure and easy control. In this study, detailed theoretical analysis of the proposed converter is made by operation intervals. A prototype with 500 W output power and 100 kHz switching frequency is realized in laboratory. It is shown that the experimental results are compatible with theoretical analysis. The efficiency of the proposed converter is 98.9% at nominal power.
Keywords: Snubbers; Zero voltage transition; Zero current transition; Boost converters; DC-DC CONVERTER; TRANSITION; DESIGN; IMPLEMENTATION; CIRCUIT; FAMILY; CELL; Engineering